The Influence of Health Education Through Social Media on Students' Knowledge about Anemia - Puspitasari, Wendy (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: The purpose of this study was to evaluate the effect of health education delivered through the social media whatsapp on increasing knowledge and changing attitudes of adolescent girls about anemia. Methodology: This study used a pre-experimental design with a one-group pretest-posttest approach. The research sample consisted of 30 grade X female students selected using a purposive sampling technique. Data were collected through questionnaires given pretest posttest the intervention. Data analysis was carried out using a parametric paired t-test to measure changes in respondents' knowledge and attitudes before and after the intervention. Main Findings: This research is effective in increasing the knowledge and attitudes of young women about anemia. The results showed a significant increase in knowledge and attitude scores after the intervention, indicating that this method could be an efficient alternative for conveying health information to adolescents. However, the limitations of the research design and limited sample require further research with a more robust design and a larger sample to confirm these findings. Novelty/Originality of this study: This study reveals the success of health education delivered through social media platforms in improving students' knowledge about anemia. By utilizing a modern communication technology approach, the results of this study indicate that information delivered in a creative and structured manner can significantly improve students' understanding of the causes, symptoms, and prevention of anemia.